The role of strategic management in the success of projects in educational institutions - Savićević Sara (Trendovi u Poslovanju)
The aim of this research is to examine the role of strategic management in the success of projects within educational institutions. The study included 159 respondents from various educational institutions, including project team members, managers, and administrative staff. The sample was selected using a random method, and all participants signed informed consent. Data were collected using the Strategic Management Importance Scale, which contains 20 statements rated on a Likert scale from 1 to 5. Hypotheses include the main hypothesis (H0) that strategic management significantly affects the success of educational projects and auxiliary hypotheses (H1 and H2) that investigate differences in attitudes based on gender and age of the respondents. The results showed that respondents generally rated the role of strategic management highly, with average scores ranging from 4.088 to 4.915. Statistically significant differences in attitudes based on gender were confirmed for most statements, while age did not show a significant impact. The conclusion of the research is that strategic management plays a crucial role in the success of educational projects, with a particular focus on improving communication and coordination among team members.